The Journey of Rolls-Royce towards Self-Directed Teams: An analysis of the Team Champion Model - Goplani, Neeta (2005)
Rolls-Royce has embarked on a journey towards Self-directed work teams. A salient feature of being self directed is giving employees the autonomy, the power to self manage, self regulate and self organize. Management have to equip the teams with the right training and development to gain all the knowledge and skills to be self-directed. A part of this has to do with transferring knowledge and skills from the functional domains to the teams. Rolls-Royce has developed a model, called the Team Champion (TC) Model that will enable and facilitate the transfer of knowledge from the functional experts to the team. This project focuses on the application of the TC model. The scope of this project is to uncover three objectives: to assess how well the TC model has been communicated and understood down the multiple layers of the organization, and the extent to which employee and managerial perceptions overlap; to assess the barriers TC model face and will face in the future and to asses the future vision of the model. A qualitative study approach is adopted where an in-depth interview with thirteen informants uncovered some of the research objectives of this study. Due to the lack of literature on transfer of knowledge from support group to teams in the teamworking domain, the author ventured into areas of knowledge transfer, team building, team development and the cultural aspect (dealing with changes in the attitudes and behaviours of employees) of teamworking. The interview findings were carefully coded and presented in themes, which were later analysed with reference to the literature review. A conclusion chapter follows which leads into a section incorporating limitations of the study.